Cooking with the cat - Worth, Bonnie; Moroney, Christopher (New York : Random House, 2003)
The Cat in the Hat bakes cupcakes in this simple retelling of a scene from the movie version of Dr. Seuss's classic books.
Preschool-kindergarten.
Accelerated Reader AR
Keywords: Cooking -- Juvenile fiction; Cats -- Juvenile fiction; Stories in rhyme